SAT0248 Calgranulins are Elevated in Spondyloarthritis and Reflect the Presence of Acute Microscopic Bowel Inflammation. (9th June 2015) - Cypers, H.; Varkas, G.; Debusschere, K.; Vogl, T.; Roth, J.; Lavric, M.; Föll, D.; Cuvelier, C.; De Vos, M.; van den Bosch, F.; Elewaut, D.
Abstract : Background: Microscopic bowel inflammation is present in about 50% of spondyloarthritis (SpA) patients. Although subclinical, it appears to be a prognostic factor in SpA, linked with more extensive disease and a less favorable outcome. At this moment, however, reliable biomarkers are missing. The calgranulins S100A8/S100A9 and S100A12 are very sensitive markers of innate immune activation. They are released from monocytes and granulocytes in the early phase of the immune response and exert prominent pro-inflammatory effects via Toll-like receptor 4 dependent mechanisms. Calgranulins can be measured in serum and stool. Moreover, the S100A8/S100A9 heterodimer, also called calprotectin, has been established for a long time as a fecal marker of disease activity in inflammatory bowel disease. Objectives: To assess whether calgranulins can be used as biomarkers for microscopic bowel inflammation in SpA. Methods: Serum calgranulin levels were measured in 122 newly diagnosed SpA patients and 39 healthy controls. SpA patients underwent an ileocolonoscopy to assess the presence of microscopic bowel inflammation. Bowel biopsies were histologically scored and subsequently immuno-stained for S100A8 and S100A9. Results: Serum levels of S100A8/S100A9 and S100A12 were significantly higher in SpA patients versus healthy controls (p<0.001). Levels correlated moderately with CRP, but not with ASDAS, BASDAI or swollen joint count. SpA patients with the acute type of microscopic gut inflammation (N=23) had significantly higher calgranulin levels compared to those with normal gut histology (N=62) (p=0.025 for S100A8/S100A9 and p=0.040 for S100A12). Furthermore, immunohistology showed high staining of S100A8 and S100A9 on acutely inflamed bowel biopsies, compared to absent/minimal staining on normal biopsies. Importantly, NSAID intake had neither influence on immunohistology nor on serum measurements. Additionally, we found that having both an elevated CRP together with an elevated S100A8/S100A9 increased the odds of having microscopic bowel inflammation with a factor of 5.4. Conclusions: Calgranulin levels, both systemically and locally, reflected the presence of acute microscopic bowel inflammation in SpA. These results also illustrate the high sensitivity of calgranulins, as they detected inflammation present only on a subclinical level. Their measurements can provide a way to identify those patients in whom further invasive checkup might be useful, as endoscopic screening of all SpA patients is not feasible in daily clinical practice. Calgranulins are therefore the first surrogate markers for subclinical bowel inflammation in SpA, allowing for more individually tailored diagnostic and therapeutic decision making. Acknowledgements: The research leading to these results has received funding from the European Union's 7th Framework Program under EC-GA No. 305266 "MIAMI". Disclosure of Interest: None declared